Avaliação de previsões de deslocamento e carga de ruptura horizontal utilizando estacas escavadas de tamanho reduzido em perfil de solo areno-siltoso - Silva, Alexandre Lima Soares (2017)
The foundations are structural elements that make up the infrastructure of the engineering works and have as main function the transmission of the requests coming from the supported structure (superstructure) to the ground in order to guarantee the stability and functionality of the same. In conventional foundation designs, such as building foundation designs, for example, only the vertical loads for load capacity and rebound calculations are generally considered. This is because the reticulated structure of these buildings, composed of monolithic beams and pylons, and the bracing structures usually contemplated in the project are sufficient to withstand the stresses caused by the horizontal loads resulting from the wind. However, in the case of foundations of bridges and foundations of machines, for example, these loads should be considered and the displacements, estimated by means of analytical methods. In addition, the bursting load must also be estimated to check for horizontal rupture safety. The present work evaluates the precision of the methods most used in the practice of projects of this nature. For this purpose, 12 cuttings of small diameter and length, isolated and in group, with block and without block of crown, were performed in the experimental field of geotechnics and foundations of the Federal University of Ceará (UFC), which were submitted to tests load test. Results of horizontal load tests performed on two 600 mm diameter continuous propeller piles were also used. From the results of laboratory and field tests, the bursting load and the displacements of the excavated piles executed, as well as of the aforementioned continuous propeller piles were predicted. The results of the predictions were compared with the results obtained from horizontal load tests (PCH's). Finally, from the results of the SHPs, values ​​of the horizontal reaction coefficient (kh) and the rate of variation of this coefficient with the depth (nh) were determined. The predictions of the horizontal displacements made were, in general, overestimated. On the other hand, the rupture load predictions were in agreement with the results of the SHPs performed. Finally, the values ​​of kh and nh determined by SHPs presented a wide range of variation and were compared with values ​​of kh and nh estimated from the NSPT.